ENHANCEMENT OF OVARIAN ACTIVITY USING CERTAIN SYNCHRONIZATION PROTOCOLS IN POSTPARTUM GRADED MURRAH BUFFALOES - PRASAD, B CHANDRA; NAIDU, G NAIDU,; SRINIVAS, M; RAGHUNATH, M; KUMAR, K ASHWINI (The Indian Journal of Animal Reproduction, 2022)
This study was aimed to observe the effect of various synchronization protocols viz. Double PGF2α, Presynch-Ovsynch, Ovsynch and CIDR-Ovsynch on fertility in postpartum sub-estrus and true anestrous graded Murrah buffaloesunder farm and field conditions and during breeding and low breeding seasons. Experimental period comprised fromSeptember 2017 to August 2019 (includes breeding and low breeding season). Presynch and Ovsynch protocolimproved the conception and pregnancy rate in sub-estrus and true anestrus buffaloes during breeding and lowbreeding seasons under farm and field condition.
Keywords: Anestrous; Buffaloes; Conception rate; Breeding season